The transformations of Godot - Busi, Frederick (University Press of Kentucky, 1980)
Didi, Gogo, Pozzo, Lucky -- the bizarre names stand out strangely against the bare-bones landscape of Waiting for Godot. In an intriguing new study of one of the most haunting plays of this century, Frederick Busi shows that these names serve important dramatic functions, reinforcing the changing roles assumed by the mysterious characters in their tortuous search for -- and avoidance of -- self. Busi also explores Beckett's convoluted literary relationship with James Joyce, especially as revealed in the plays-within-the-play and verbal jigh jinks of Finnegan's Wake, where, as in Godot, the.